THE OBLIGATION OF SPOUSES TO CONTRIBUTE TO HOUSEHOLD COSTS - Ramazani Babola Niclette; Kelekele Itamili Frida (IJRDO - Journal of Business Management, 2024)
Marriage is a legal institution. It produces both legal and social effects. Legally, in marriage, we find a father (husband), a mother (wife), and children living under the same roof. Of course, while among these children are the mentally incapacitated and insane, they cannot live apart from their parents because they are part of the household. The household needs to flourish. This is because our Congolese legislature decided that spouses each have the obligation to contribute to household expenses. Since the spouses’ contribution to household expenses is an obligation, they must contribute positively. However, sometimes only one spouse can take on this responsibility alone; this is very often the case in the current mentality where it is seen that only the man should contribute to the household expenses. This is why we deemed it useful to conduct this study. The existence of a joint household presupposes constant and simultaneous support, a reciprocal collaboration in these responsibilities, for which each spouse is responsible according to their means. Undoubtedly, this support only becomes effective if each spouse contributes materially, financially, or even intellectually. This topic has been the subject of previous studies, notably those discussed below.